Implementação de uma fog computing para fornecer StaaS a dispositivos IoT utilizando sistemas embarcados - Machado, José dos Santos (2018)
IoT (Internet of Things) needs many services to be a reality because it has a very restricted processing and storage resource, its interconnection with Cloud Computing is a relevant, high attention factor for researchers worldwide. The issues of latency, big data, storage and processing power close to edge devices, led the emergence of Fog Computing. Fog Computing is the interconnection between IoT devices and Cloud Computing, and it can bring processing and storage power to IoT devices, and it enables the emergenc of new technologies and applications to solve these shortcomings. This study presents the concept of Fog Computing, its challenges, its theoretical contextualization, the related works together with the systematic review and performs the implementation and analysis of a Fog Computing, to provide StaaS (Storage as a Service), IoT devices using platforms systems and compares their results with those achieved by a high-performance server. It develops the FogSys system with the main objective of simulating, receiving, validating and storing the data of IoT devices to be transferred to Cloud Computing, functioning as a Fog Computing to provide the service of StaaS (Storage as a Service). The results showed that the implementation of this service in devices of embedded systems is a good alternative to reduce one of these problems, in this case, the data storage, which reaches IoT devices today.